REPORTING ISSUES IN THE AREA OF CORPORATE SOCIAL RESPONSIBILITY IN THE LIGHT OF LEGAL PROVISIONS AND PRACTICAL EXPERIENCE (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Abstract. In recent years in Poland there has been a new direction in the system for enterprises to report their achievements  in the field of corporate social responsibility tasks.   The institutional framework for this trend is provided by new EU and polish regulations referring to non-financial reporting of enterprises. These define a clear course towards more business transparent and environmental responsibility. The implementation of thise new  regulations began quite recently. This situation therefore inspired this paper. Its aim is to present the system of CSR reporting and comment on it in terms of the practical  experiences. The materials used in the article include subject literature, legal acts and published results of research CSR reporting in practise. The research encompassed legal regulations in force on 31 December 2018.
Keywords: CSR, non-financial information, reporting standards, EU directives.